Effect of Macroeconomic Variables on Financial Performance of Healthcare Manufacturing Firms in Nigeria - Dr. Ifeyinwa Elizabeth NNAJIEZE; Anthony Okorie Nwabuisi; Alex Onyeji Igwe (Asian Journal of Finance & Accounting, 2024)
This study empirically investigated the effect of macroeconomic variables on financial performance in Nigeria healthcare sector. It spanned from 2008 to 2018 and utilized annual time series secondary data extracted from annual reports and financial statements of the selected firms. The ex-post facto research design was adopted while analytical techniques employed were descriptive statistics, fully modified ordinary least squares panel regression and Pearson correlation analysis. Findings revealed that changes in macroeconomic indices play significant roles in the financial position of Healthcare manufacturing firms in Nigeria. Particularly, the result showed that exchange rate, interest rate, external debt and trade openness have a negative effect while inflation rate exerts a positive influence on the financial position of Healthcare manufacturing firms in Nigeria. Among the selected macroeconomic variables, the effects of exchange rate and inflation rate were significant. The result implies that an unstable macroeconomy is harmful to the healthy growth of Healthcare manufacturing firms in Nigeria. The study, therefore, recommended among other things that the exchange rate should be monitored while economic policy measures aimed at controlling the exchange rate in Nigeria should be established. A high rate of interest should also be regulated and set to a rate favourable to the growth of Healthcare manufacturing companies in Nigeria. The federal government of Nigeria should work towards reducing their level of borrowing from foreign countries and as well reduce the volume of trade openness for the overall performance of the manufacturing sector in Nigeria.